EFEK LEVEL PROTEIN KASAR DALAM COMPLETE FEED UNTUK PENGGEMUKAN KAMBING HIBRID BOERPE - Usman Ali; Muhammad Abdul Adhim; Inggit Kentjonowaty (Universitas Tribhuwana Tunggadewi, 2022)
This research aims to analyze the dose of crude protein in complete feed on feed intake, body weight gain (BWG), conversion, and feed efficiency in fattening BoerPE hybrid goats. The experimental method used a randomized design with three treatments and three groups. The treatment was 11% CP dose (T1), 13% CP dose (T2), and 15% CP dose (T3), and the BW group (Kg) G1 = 21.8; G2 = 28.4 and G3 = 31.7. Then the variance of data analysis and the Least Significant Difference Test (LSDT). The results showed that the dose of CP feed did not affect feed intake but was very significant for BWG, feed conversion, and feed efficiency. The BW group had a significant effect on feed intake and BWG, feed conversion, and feed efficiency. In the treatment, the average feed intake increased from 1.11 to 1.16 Kg/head/day; BWG increased from 96.55 to 132.22 g/head/day, feed conversion decreased from 11.52 to 8.77, and feed efficiency increased from 8.68 to 11.42; while, in the BW group, the average feed intake increased from 1109.17 to 1179.26; BWG increased by 107.77 to 123.68 g/head/day; feed conversion decreased from 10.42 to 9.66; feed efficiency increased from 9.72 to 10,49 (%). In conclusion, increasing the dose of crude protein in complete feed can increase body weight gain and feed efficiency, then the use of a 15% CP dose in optimal feed can increase BWG and feed efficiency.